Sensory Phenotypes for Balance Dysfunction After Mild Traumatic Brain Injury. (2nd August 2022) - Fino, Peter C.; Dibble, Leland E.; Wilde, Elisabeth A.; Fino, Nora F.; Johnson, Paula; Cortez, Melissa M.; Hansen, Colby R.; van der Veen, Susanne M.; Skop, Karen M.; Werner, J. Kent; Tate, David F.; Levin, Harvey S.; et al.
Abstract : Background and Objectives: Recent team-based models of care use symptom subtypes to guide treatments of individuals with chronic effects of mild traumatic brain injury (mTBI). However, these subtypes, or phenotypes, may be too broad, particularly for balance (e.g., vestibular subtype). To gain insight into mTBI-related imbalance, we (1) explored whether a dominant sensory phenotype (e.g., vestibular impaired) exists in the chronic mTBI population, (2) determined the clinical characteristics, symptomatic clusters, functional measures, and injury mechanisms that associate with sensory phenotypes for balance control in this population, and (3) compared the presentations of sensory phenotypes between individuals with and without previous mTBI. Methods: A secondary analysis was conducted on the Long-Term Impact of Military-Relevant Brain Injury Consortium—Chronic Effects of Neurotrauma Consortium. Sensory ratios were calculated from the sensory organization test, and individuals were categorized into 1 of the 8 possible sensory phenotypes. Demographic, clinical, and injury characteristics were compared across phenotypes. Symptoms, cognition, and physical function were compared across phenotypes, groups, and their interaction. Results: Data from 758 Service Members and Veterans with mTBI and 172 individuals with no lifetime history of mTBI were included. Abnormal visual, vestibular, and proprioception ratios were observed in 29%, 36%, and 38% of people with mTBI, respectively, with 32% exhibiting more than 1 abnormal sensory ratio. Within the mTBI group, global outcomes ( p < 0.001), self-reported symptom severity ( p < 0.027), and nearly all physical and cognitive functioning tests ( p < 0.027) differed across sensory phenotypes. Individuals with mTBI generally reported worse symptoms than their non-mTBI counterparts within the same phenotype ( p = 0.026), but participants with mTBI in the vestibular-deficient phenotype reported lower symptom burdens than their non-mTBI counterparts (e.g., mean [SD] Dizziness Handicap Inventory = 4.9 [8.1] for mTBI vs 12.8 [12.4] for non-mTBI, group × phenotype interaction p < 0.001). Physical and cognitive functioning did not differ between the groups after accounting for phenotype. Discussion: Individuals with mTBI exhibit a variety of chronic balance deficits involving heterogeneous sensory integration problems. While imbalance when relying on vestibular information is common, it is inaccurate to label all mTBI-related balance dysfunction under the vestibular umbrella. Future work should consider specific classification of balance deficits, including specific sensory phenotypes for balance control.